Evaluating Village-owned Enterprises and SMEs Businesses Engagement Through Web Application Using System-Usability Scale - Ariq Cahya Wardhana; Fauzan Romadlon; Gita Fadila Fitriana; I Anna Tul Munikhah; Novian Adi Prasetya; Aiza Yudha Pratama; Ade Yanyan Ramdhani; Suparyo Suparyo (STMIK Budi Darma, 2022)
Village-owned enterprises (BUMDesa) and Small and Medium Enterprises (SMEs) are enabled to strengthen the rural economy. The two entities shall collaborate and will help the rural economy become more adaptive and sustainable. One approach to collaborate is using digital technology, such as web applications. It will allow businesses to survive by gaining potential networking and cross-border markets through online marketing. This collaboration can be done using a digital technology approach where both roles are needed to improve the village economy. If this technological approach is not implemented, then marketing will be limited so that it will have an impact on the village economy. The qualitative and scrum approach is used to develop the digital web. The result shows differences between BUMDesa and SMEs' roles toward the web application. BUMDesa can make better managerial through digital businesses so that BUMDesa can accelerate SMEs' productivity by opening new markets and business perspectives to SMEs. The testing process is carried out to prevent the failure of website development by implementing a usability test, namely the Usability Scale (SUS) System. The tests carried out show that the proposed design gets a good score of 69.63, so it is effective and efficient to be implemented in website development. SMEs can gain a broader market, improve their production standard, and add production capacities. The collaboration will map and profile their strengths and weaknesses to minimize the implementation gap. In addition, the BUMDesa and SMEs will invest in social capital, which means the ability to establish cooperation, trust, and participation, in the local community to benefit from the social network. It will improve innovation capability